A Case of Post-Traumatic Coronary Occlusion - Lee, Hwa Young (Korean J Intern Med, 1991)
Several cases of transmural myocardial infarction(1–11)) and ventricular aneurysm(12–14)) caused by a blunt trauma of the chest have been reported. Nevertheless, the cases documented with coronary and ventricular angiography are very few(5,8–11,14)). There has always been a debate over the etiological mechanism of such lesions. Since in some cases there was no evidence of coronary lesions(5,9,11,14)), it was postulated that they were produced by direct myocardial contusion, but in other instances the evidence of coronary occlusion was angiographically(8,10)) and pathologically(2,3)) proved. We experienced a case of acute myocardial infarction with ventricular aneurysm secondary to nonpenetrating chest trauma by an umbrella tip and wish to report this unusual case, along with a review of the literature.